Plant, Soil and Microbes 2016
DOI: 10.1007/978-3-319-29573-2_7
|View full text |Cite
|
Sign up to set email alerts
|

Response of PGPR and AM Fungi Toward Growth and Secondary Metabolite Production in Medicinal and Aromatic Plants

Abstract: Plant growth-promoting rhizobacteria (PGPRs) are a group of naturally occurring benefi cial soil bacteria that colonize with the plant root system and promote growth by triggering the production of growth-regulating substances and facilitate the plants in the uptake of essential nutrients from the surrounding environments. Similarly, arbuscular mycorrhizal (AM) fungi also enhanced the growth, water and nutrient uptake, and especially available phosphate through their specialized hyphae. In addition, PGPR and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 88 publications
(76 reference statements)
1
10
0
Order By: Relevance
“…In the present study, all the isolates showed positive for the production of ammonia. The accumulation of ammonia alters the soil's pH to alkaline and, thereby, inhibits the germination of fungal spores and the suppression of phytopathogenic fungi [44]. Our study confirmed the variations in the production of ACC deaminase and the hydrolytic enzymes, such as protease, cellulase, and amylase, among the isolates used in the study (Tables 1 and 2).…”
Section: Discussionsupporting
confidence: 79%
“…In the present study, all the isolates showed positive for the production of ammonia. The accumulation of ammonia alters the soil's pH to alkaline and, thereby, inhibits the germination of fungal spores and the suppression of phytopathogenic fungi [44]. Our study confirmed the variations in the production of ACC deaminase and the hydrolytic enzymes, such as protease, cellulase, and amylase, among the isolates used in the study (Tables 1 and 2).…”
Section: Discussionsupporting
confidence: 79%
“…It suppresses the growth of certain fungi and nitrobacteria as it has potent inhibition effect. It also disturbs the equilibrium of the microbial community and inhibits germination of spores of many fungi (Swamy et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, microorganisms can act as elicitors and increase the production of secondary metabolites involved in the biological and pharmaceutical activity of medicinal plants (Mohammadi et al, 2017), such as flavonoids and terpenes content, phenolic compounds, microbial activity, chlorophyll content, nutrient uptake, plant growth and development (Banchio et al, 2008;Cappellari et al, 2013;Zhao et al, 2016;Damam et al, 2016;Swamy et al, 2016).…”
Section: Application Of Plant Growth Promoting Microorganismsmentioning
confidence: 99%
“…In addition to the rhizobacterium applied as elicitors, arbuscular mycorrhizal fungi (AM) can help to improve the physical, chemical and structural properties of the soil. By increasing the availability of phosphorus through its specialized hyphae, the organic matter content and reduction of the apparent soil density (Yousefi et al, 2011;Akhazari et al, 2015), water retention by stimulating the plant's root system to exploit greater soil volume and to assist in the accumulation of secondary metabolites (Swamy et al, 2016).…”
Section: Influence Of Microrganisms On Phytochemical Compositionmentioning
confidence: 99%